Determinants of attitude towards and purchase intention of private label brands in Ecuador - Macías, Washington; Arias Bayona, Angie; Bollorino Montoya, Sharon; Sanga Hernandez, Lissette (Revista Venezolana de Gerencia, 2023)
The purpose of this study is to explain which factors influence the attitude towards private label products and their purchase intention in Ecuador. In this regard, the hypothetical effects of store image, familiarity with the private brand, its perceived quality and risk, and customers’ price consciousness, are studied. A survey distributed online was implemented, obtaining a final sample of 224 customers of the main supermarket chain in Ecuador: Supermaxi. A Confirmatory Factor Analysis was performed, and a structural equations model was tested by consistent Partial Least Squares. Among the most relevant findings, it was found that attitudes towards private brands are a critical determinant of purchase intention; that a better image of the supermarket reduces the perceived risk, fostering consumer’s purchase intention. Familiarity with the private brand positively affects perceived quality, which, along with price consciousness, contributes to building attitudes towards private brands. Taken together, these results suggest that supermarkets should work on the tangible and intangible aspects that create store image to contribute to private brands sales. We also recommend marketing tactics such as product samples and testimonials to build brand familiarity among consumers, which along with meeting quality expectations will improve attitudes toward and purchase intention of private label brands. Finally, supermarkets need to be aware of those product categories in which consumers are most price-conscious in order to highlight the savings derived from private label products and promote more sales.